Trotsky's notebooks, 1933-1935 : writings on Lenin, dialectics and evolutionism - Pomper, Philip; Felshtinsky, Yuri (New York : Columbia University Press, 1986)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Trotski, Leon